2008
DOI: 10.1021/la704002y
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Attachment of Organic Monolayers to Silicon Carbide Surfaces

Abstract: This work presents the first alkyl monolayers covalently bound on HF-treated silicon carbide surfaces (SiC) through thermal reaction with 1-alkenes. Treatment of SiC with diluted aqueous HF solutions removes the native oxide layer (SiO2) and provides a reactive hydroxyl-covered surface. Very hydrophobic methyl-terminated surfaces (water contact angle theta = 107 degrees ) are obtained on flat SiC, whereas attachment of omega-functionalized 1-alkenes also yields well-defined functionalized surfaces. Infrared re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
130
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(144 citation statements)
references
References 57 publications
12
130
0
2
Order By: Relevance
“…While pristine, freshly prepared hydroxyl-terminated SiC is strongly hydrophilic, with water contact angle for Si-face surface being only ~15° [94], exposure to environmental conditions and chemical cleaning leads to formation of stable C-O-C bonds, which unavoidably increases hydrophobicity of the SiC, and so the values similar to the one demonstrated in Figure 7a become rather typical. When carbon bonds appear on top of SiC (including formation of an IFL), the relative hydrophilicity decreases and the contact angle increases [94,95], though still remaining significantly less hydrophobic than in MLG or graphite. In the case of epitaxial graphene, the wetting properties of a thin graphene layer are dominated by SiC and the IFL (in case of SiC(0001)), which essentially results in a more hydrophilic graphene than that predicted.…”
Section: Discussionmentioning
confidence: 58%
“…While pristine, freshly prepared hydroxyl-terminated SiC is strongly hydrophilic, with water contact angle for Si-face surface being only ~15° [94], exposure to environmental conditions and chemical cleaning leads to formation of stable C-O-C bonds, which unavoidably increases hydrophobicity of the SiC, and so the values similar to the one demonstrated in Figure 7a become rather typical. When carbon bonds appear on top of SiC (including formation of an IFL), the relative hydrophilicity decreases and the contact angle increases [94,95], though still remaining significantly less hydrophobic than in MLG or graphite. In the case of epitaxial graphene, the wetting properties of a thin graphene layer are dominated by SiC and the IFL (in case of SiC(0001)), which essentially results in a more hydrophilic graphene than that predicted.…”
Section: Discussionmentioning
confidence: 58%
“…No signs of the formation of ordered adsorbate layers were observed (Seino et al, 2002). Rosso et al (Rosso et al, 2008) reported the thermal formation of alkyl monolayers from alkenes on hydroxyl-terminated surfaces as depicted in Fig. 10.…”
Section: Surface Functionalizationmentioning
confidence: 99%
“…The UV-induced formation of monolayers of semi-carbazide on H-terminated Si 5 N 4 surfaces prepared under UHV conditions was also reported by Coffinier et al [Coffinier, et al, 2007]. In addition, methyland ester-terminated monolayers were also formed on Si 3.9 N 4 [Arafat, et al, 2004] and 3C-SiC substrates [Rosso, et al, 2008b& Rosso, et al, 2009, using wet etching with HF and UV irradiation in the presence of alkenes, under ambient conditions of temperature and pressure. Semi-carbazides and esters can be easily converted to amine [Coffinier, et al, 2007] and acid groups [Rosso, et al, 2009], respectively, which can serve for further attachment of biomolecules or biorepelling molecules and polymers [Asanuma, et al, 2006& Coffinier, et al, 2005& Love, et al, 2005a.…”
Section: Organic Monolayers On the Surfaces Of Silicon-rich Materialsmentioning
confidence: 64%
“…Semi-carbazides and esters can be easily converted to amine [Coffinier, et al, 2007] and acid groups [Rosso, et al, 2009], respectively, which can serve for further attachment of biomolecules or biorepelling molecules and polymers [Asanuma, et al, 2006& Coffinier, et al, 2005& Love, et al, 2005a. The advantage of alkene-based monolayers is their stability, mainly due to the absence of a silicon oxide layer, and the presence of stable and non-polar Si-C bonds, in the case of Si [Linford & Chidsey, 1993] and Si x N 4 , [Arafat, et al, 2007] [Rosso, et al, 2008b] and stable C-O-C bonds in the case of SiC surfaces [Rosso, et al, 2008a]. Stability measurements revealed the outstanding stability of thermally produced 1-hexadecene monolayers on Si x N 4 substrates, in acidic or basic conditions at 60 ºC, with changes in contact angles of less than 5º after 4 h of such a treatment [Arafat, et al, 2007].…”
Section: Organic Monolayers On the Surfaces Of Silicon-rich Materialsmentioning
confidence: 99%
See 1 more Smart Citation